Clinical Significance of Down-Regulated CD70 and CD27 Expression in Poor Prognosis of Esophageal Squamous Cell Carcinoma - Shan T; Zhao X; Zhang Z; Wang J; Zhang Y; Yang Y; Zhao S (Cancer Management and Research, 2020)
Ting-ting Shan,1,* Xuan Zhao,2,* Zhen Zhang,2,* Jing-pu Wang,1 Yi Zhang,2 Yang Yang,1 Song Zhao1,3 1Department of Thoracic Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, People’s Republic of China; 2Biotherapy Center, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, People’s Republic of China; 3School of Medical Sciences, The Key Laboratory of Thoracic Tumor of Zhengzhou City, Zhengzhou 450052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Song ZhaoDepartment of Thoracic Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, People’s Republic of ChinaTel +86 1 367 366 5008Email 13673665008@163.comYi ZhangBiotherapy Center, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan 450052, People’s Republic of ChinaTel +86 1 513 892 8971Email yizhang@zzu.edu.cnIntroduction: CD27 is a co-stimulatory immune checkpoint molecule in the tumor necrosis factor receptor superfamily. CD27 regulates the generation and maintenance of T cell immunity by binding to CD70 and regulating B-cell activation and immunoglobulin synthesis.Materials and Methods: CD27 and CD70 expression were assessed in esophageal squamous cell carcinoma (ESCC) compared to normal tissue samples in the GSE53625 dataset of 179 paired cases and in 153 Chinese cases using reverse transcription quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry. The correlation was also investigated between CD27 and CD70 expression and immune-related pathways, including CD8+ T cell recruitment, function, and other inhibitory immune checkpoints.Results: Levels of both CD27 and CD70 expression were down-regulated in ESCC compared to the paired normal tissues. CD27 and CD70 expression was mainly present in lymphocytes surrounding and infiltrating the tumor lesions but rarely expressed in tumor cells. Lost expression of CD27 and CD70 was associated with clinicopathological features, including depth of tumor invasion and better patient survival. Furthermore, CD27 expression was significantly associated with levels of CD8A, GZMB, IFNG, the CD8+ T cell recruitment-associated chemokines (CXCL9, CXCL10, and CXCL11), and CD8 receptors (CCR5, CXCR6, and CXCR3), while CD70 expression was inversely associated with levels of immunosuppressive checkpoints (PD-L1, PD-L2, and HHLA2).Conclusion: Detection of CD70/CD27 expression could be further verified as a biomarker for ESCC early detection and prognosis prediction.Keywords: esophageal cancer, CD27, CD70, biomarker, prognosis